2014
DOI: 10.1007/s10549-014-3236-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo anti-metastatic effects of uPAR retargeted measles virus in syngeneic and xenograft models of mammary cancer

Abstract: Purpose The urokinase receptor (uPAR) plays a critical role in breast cancer (BC) progression and metastases, and is a validated target for novel therapies. The current study investigates the effects of MV-uPA, an oncolytic measles virus fully retargeted against uPAR in syngeneic and xenograft BC metastases models. Methods In vitro replication and cytotoxicity of MVs retargeted against human (MV-h-uPA) or mouse (MV-m-uPA) uPAR were assessed in human and murine cancer and non-cancer mammary epithelial cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…As expected, from prior reports by us [23, 24], MV-h-uPA and MV-m-uPA infected human MDA-MB 231 and murine 4T1 tumor cells in a species specific manner, while non-cancer epithelial cells (HMEC, NMuMG) were not susceptible to viral infection (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As expected, from prior reports by us [23, 24], MV-h-uPA and MV-m-uPA infected human MDA-MB 231 and murine 4T1 tumor cells in a species specific manner, while non-cancer epithelial cells (HMEC, NMuMG) were not susceptible to viral infection (Fig. 1).…”
Section: Resultssupporting
confidence: 89%
“…Similar species specific effects were observed in human HT-29 and T47D, as well as murine CT-26 cancer cells. As previously reported [24], MV-h-uPA was more selective to human cancer than non-cancer epithelial cells (HMEC) than MV-GFP.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Retargeted viruses, via single-chain antibodies, have been developed, thus far, against tumor cell specific targets including: CD38, epidermal growth factor (EGFR), EGFR mutant vIII, alpha folate receptor [9193], CD133 [94], insulin-like growth factor receptor 1 [93], CEA [95], CD20 [80], prostate-specific antigen [85], and the urokinase receptor [96,97]. MV strains displaying cytokines, such as IL-13 and thus targeting the glioma specific interleukin-13 receptor alpha2, were also successfully created [98].…”
Section: Improving the Oncolytic Efficacy And Safety Of MV Strainsmentioning
confidence: 99%
“…We have previously developed and characterized novel, species specific oncolytic MVs fully retargeted against the human or murine urokinase receptor (uPAR) [17,18], a GPI-anchored cell surface receptor, which is overexpressed in tumor and particularly in stromal cells, and whose role in tumor-stromal interactions and cancer progression are well established [19][20][21][22][23][24][25]. We demonstrated that systemic 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 3 10 4 10 5 10 6 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 10 2 10 3 10 4 10 5 administration of species specific, human (MV-huPA) or murine (MV-muPA) uPAR retargeted MVs is safe, successfully targets tumor tissues over non-cancer tissues, and is associated with significant tumor delaying effects in primary or metastatic, xenograft, and syngeneic cancer models, respectively [18,26]. Taking advantage of the species specificity of MV-muPA, we recently reported that (murine) stromal-selective MV-muPA was associated with direct stromal targeting in a human breast cancer xenograft (where human cancer cells are not permissive to the murine targeted virus), leading to modulation of murine stromal gene expression, indirect effects on tumor cell gene expression, and measurable in vivo tumor growth delay by MV-muPA [27].…”
Section: Introductionmentioning
confidence: 99%